Pro SharePoint 2010 Governance - Wright, Steve; Erkes, Corey (Apress : Imprint: Apress, 2012)
Pro SharePoint 2010 Governance is the first book on the market focusing exclusively on the essential guidance necessary for leveraging SharePoint 2010 within your organization's intranet, extranet or Internet environment for maximum business value. Effective governance allows your organization to promote the adoption of SharePoint's productivity-enhancing features while maintaining security and control over your organization's most vital information. Pro SharePoint 2010 Governance presents comprehensive guidance, from the basics of "What is governance?" to the detailed considerations of IT, information and application management. Using the conceptual framework promoted by Microsoft and augmented with detailed discussions, recommendations and checklists, you will have all the information you need to streamline the governance of your SharePoint sites. Teaches the concepts and benefits of SharePoint site governance. Discusses advanced features and techniques for implementing governance in your organization. Provides detailed recommendations, templates and checklists for jump-starting your governance effort.